Pediatric Adrenocortical Tumors: What They Can Tell Us on Adrenal Development and Comparison with Adult Adrenal Tumors - Lalli, Enzo; Figueiredo, Bonald C. (Frontiers in Endocrinology, 2015)
Adrenocortical tumors (ACT) in children are very rare and are most frequently diagnosed in the context of the Li-Fraumeni syndrome, a multiple cancer syndrome linked to germline mutations of the tumor suppressor gene TP53 with loss of heterozygosity in the tumors. A peak of children ACT incidence is present in the states of southern Brazil, where they are linked to the high prevalence in the population of a specific TP53 mutation (R337H). Children ACT have specific features distinguishing them from adult tumors in their pathogenetic mechanisms, genomic profiles and prognosis. Epidemiological and molecular evidence suggests that in most cases they are derived from the fetal adrenal.